Comprehending Public Means of Conditioning the Realization of Public Purpose in Poland - Feret, ElÅ¼bieta (European Scientific Journal, ESJ, 2017)
The subject of the article is very important in Poland, especially now that Poland has a lot of expenditures from budget. The problems which are present include polish solution, and they are the basis for further regulations. According to the accepted title, the study was devoted to the review of important issues connected with public means in Poland. One should regard as basic this type of financial means conditioning. Also, they should determine the completion of the so-called purpose/tasks public. Due to the adopted subject, the study is presenting in the only selective way, cardinal regulations concerning the accumulation and disbursing of public means by entities and by law. This was described based on the annual financial plan whereby Poland are accepting the character of one central budget - state budget and self-government budgets - of individual communes, districts, and provinces. Conducted deliberations have also supported the chosen positions of literature. Thus, they end with the motions of the Author.